Midwives' voices need to be heard in the safeguarding discussion. (2nd September 2019) - Sanders, Michael; Reid, Louise
Abstract : Midwives meet women at a crucial stage of life, and can influence a child's wellbeing before it has been born. Michael Sanders and Louise Reid explain how midwives can help safeguard children